2016
DOI: 10.1016/j.jacep.2015.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Peri-Mitral Atrial Tachycardia Using the Marshall Bundle Epicardial Connections

Abstract: PMAT-LOMs following PVI or valve surgery accounted for up to 11% of PMATs. The bidirectional block of either MB-LA or CS-MB connections is required to eliminate PMAT-LOMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 14 publications
1
52
0
Order By: Relevance
“…MAFL is commonly encountered after atrial fibrillation ablation and terminated by creating linear lesion sets across the MI, although epicardial structures like the vein of Marshall and coronary sinus may serve as a barrier for MI ablation transmurality. 2,4,5 While an anterior line is predominantly performed targeting thinner atrial myocardium, the thickness of epicardial structures in the region of BB is a barrier to achieving completely transmural lesions.…”
Section: Discussionmentioning
confidence: 99%
“…MAFL is commonly encountered after atrial fibrillation ablation and terminated by creating linear lesion sets across the MI, although epicardial structures like the vein of Marshall and coronary sinus may serve as a barrier for MI ablation transmurality. 2,4,5 While an anterior line is predominantly performed targeting thinner atrial myocardium, the thickness of epicardial structures in the region of BB is a barrier to achieving completely transmural lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The vein or ligament of Marshall, is an anatomical structure related to atrial tachyarrhythmia . The Marshall bundle is reported to be involved with complex atrial tachycardia (AT) by bridging endocardial activation . Ethanol infusion is one strategy to treat Marshall bundle‐related atrial tachycardia (MB‐AT) .…”
Section: Introductionmentioning
confidence: 99%
“…Perimitral AT with an epicardial connection involving the VOM has been reported. 1 The role of the VOM was demonstrated during pacing 2 ; however, no activation map during tachycardia previously has been reported. All authors have reported that they have no relationships relevant to the contents of this paper to disclose.…”
mentioning
confidence: 92%